Biofilm-based biocatalysis for β-cyclodextrin production by the surface-display of β-cyclodextrin glycosyltransferase in Bacillus subtilis - Dan Wang; Sinan Wang; Wenjun Sun; Tianpeng Chen; Caice Liang; Pengpeng Yang; Qingguo Liu; Chunguang Zhao; Yong Chen (Scientific Reports)
Abstract β-cyclodextrin (β-CD) is an important cyclic oligosaccharide, which is widely applicated in foods, environmental protection, and cosmetics, primarily prepared from enzymatic synthesis in traditional industry. However, several challenges persist, including cumbersome processes and difficulties in achieving continuous fermentation and catalysis. This research introduced a biofilm-based immobilized fermentation, integrating with enzyme catalysis system of surface display in Bacillus subtilis. The bslA gene was selected to construct the surface display system due to its ability to promote biofilm formation and serve as an anchorin. Compared to free cell catalysis, the biofilm-based immobilized catalysis expanded the temperature range to 40–70 and the pH range to 5–7.5. During the continuous catalysis process, by the 13th batch, the relative activity remained around 52%, and the conversion rate exceeded 36%, similar to the single-batch free cell catalysis. These findings provide valuable insights and effective strategies for the industrial production of β-CD and other biochemicals through continuous catalysis.